Comparison of cognitive impairments with lipid profiles and inflammatory biomarkers in unipolar and bipolar depression. (June 2022) - Zhang, Shu-Fang; Chen, Hua-Min; Xiong, Jia-Ni; Liu, Jun; Xiong, Jie; Xie, Jia-zhao; Wang, Xiao-Ming; Tian, Qing; Xia, Bin; Li, Yi; Qu, Na
Abstract: Cognitive impairments is one of important accompanied symptom in Unipolar depressive disorder (UD) and bipolar disorder (BD) that was hard to distinguish, as their diagnosis is based on behavioural observations and subjective symptoms. In this study, we could highlight the difference of cognitive ability in UD and BD by testing lipid profiles and inflammatory biomarkers in major depressive episodes (MDE). 207 subjects (96 unipolar and 111 bipolar depressed patients) were included in this study. We applied Montreal Cognitive Assessment (MoCA) to test cognitive ability. The 24-item Hamilton Depression Rating Scale was used for assessment at the beginning of treatment. A series of clinical variables and lipid profiles were collected from clinic record. We detected pro-inflammatory biomarkers Interleukin-1β (IL-1β), Interleukin-6 (IL-6), C-reaction protein (CRP) levels and brain-derived neurotrophic factor (BDNF) by enzyme linked immunosorbent assay. From the results, cognitive impairments were more popular in BD than UD, most obviously in severe cognitive impairments (MoCA score<23). And UD showed better cognitive ability than BD in MoCA, particularly in language domain. Compared lipid profiles like total cholesterol (TC), triglycerides (TG), high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C), apolipoprotein A1 (ApoA1), Apolipoprotein B (ApoB) and lipoprotein α (Lpα), we found that ApoB was higher in BD than UD that maybe a risk factor in cognition. There was no obviously difference in TC, TG, HDL-C, LDL-C, ApoA1, or Lpα. Also, we found CRP level in BD was higher than UD, and showed no significant difference in IL-1β and IL-6 levels. Furthermore, BDNF level which was neurotrophic biomarker for cognition and mood was significantly declined in BD compared with UD. Correlation analysis showed that ApoB and CRP was negative closed associated with MoCA scores. And BDNF level was positive related with cognitive ability in MDE patients. From our results mentioned that quantitative lipid profiles and inflammatory biomarkers analysis might help to objectively identify between these disorders and up our understanding of their pathophysiology. And ApoB, CRP and BDNF could be as potential peripheral candidates in cognitive evaluation to distinguish UD and BD.